Enhancing Life Science Skills in Early Childhood Through Culturally Relevant Project-Based Learning: A Quasi-Experimental Study - Ramadhani, Nurhidayah; Intisari; Nur Alim Amri; Akib, Tasrif; Hajerah (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Project-Based Learning (PJBL) has gained recognition as an effective pedagogical approach for fostering active learning, scientific literacy, and problem-solving skills in early childhood education. However, empirical studies on its application in culturally relevant contexts remain limited. This study examines the effectiveness of PJBL in developing life science skills among children aged 5–6 years through the "Pisang Goreng" (fried banana) experiment, a hands-on learning activity grounded in local culture. A quasi-experimental one-group pretest-posttest design was employed, involving 15 purposively selected kindergarten students. The intervention included planting, harvesting, and processing bananas, enabling children to engage with biological processes through experiential learning. Data were collected using observation scales, portfolio evaluations, and performance-based assessments. A paired-sample t-test revealed a statistically significant improvement in children's cognitive, problem-solving, and critical thinking abilities, with a substantial effect size (Cohen’s d = 1.25). These findings suggest that PJBL enhances life science skills by integrating culturally meaningful experiences into early childhood education. Despite its contributions, the study is limited by its small sample size and single-site implementation, restricting the generalizability of results. Future research should explore PJBL’s effectiveness across diverse educational settings and its applicability to broader STEM domains, employing larger samples and longitudinal designs to strengthen the empirical foundation for scalable, culturally adaptive PJBL frameworks in early childhood science education. This study underscores the importance of experiential, inquiry-based learning in fostering scientific literacy and critical thinking among young learners.